Influence of Mg Incorporation on the Structural and Electrochemical Properties of LiMn1-xMgxO2 Cathode Material for Lithium-Ion Batteries - Hassan, Nour Abd Alrazaq; Al-Timimi, Muhammad Hameed (Science and Technology Indonesia, 2025)
In this study, the urea route technique was used to synthesize LiMn1-xMgxO2 compounds with (x = 0, 0.125, 0.25, 0.375, 0.5, 0.625, and 0.75 wt.%) as cathode active materials for lithium-ion batteries. All prepared samples underwent structural and morphological analysis. The X-ray diffraction (XRD) results showed a single-phase crystal structure for the synthesized nanoparticles. The crystalline size (D111) of the produced particles was calculated using Debye-Scherrer’s equation, and the results indicated only a slight change in particle size upon substitution of magnesium ions. Fourier transform infrared spectroscopy (FTIR) analysis revealed several vibrational modes, including (O-H and C=O). Field emission scanning electron microscopy (FESEM) images also revealed that the nanoparticles were cubic, with little variation in size distribution. The synthesized LiMn1-xMgxO2 was further characterized by energy dispersive X-ray (EDX) spectroscopy. The findings confirmed the presence of magnesium (Mg), manganese (Mn), and oxygen (O). Electrochemical testing was conducted only on samples of LiMn1-xMgxO2 (x = 0, 0.125, and 0.75 wt.%). Electrochemical experiments showed that LiMn1-xMgxO2 (x = 0.125 and 0.75 wt.%) exhibited greater charge and discharge capacities than the LiMnO2 electrode. These results were consistent with the findings from electrochemical impedance spectroscopy (EIS). Overall, the electrochemical experiments demonstrated that LiMn1-xMgxO2 (x = 0.125 and 0.75 wt.%) performed better than LiMnO2.